Numerical scheme for dynamic response of deep-water risers (2006)
ABSTRACT: A numerical scheme for dynamic response of deep-water risers is presented in this paper; its formulation is based on the Finite Element Method (FEM) and the quasi-steady model for prediction of the transverse forces. The increased mean drag coefficient during lock-in is also considered in the numerical scheme. The simulation results are compared to experimental data obtained from a 35-meter long flexible riser model. Good agreement is observed in these comparisons. The in-line response of the riser model is well represented by the numerical scheme and the transverse response is under-predicted as the oscillating frequency increases.